(untitled) (Revista Sistemas de Producción Agroecológicos, 2025)
Short marketing circuits (SCC) are a social and sustainable proposal for the circulation and marketing of agroecological products within local markets. From this perspective, the CCCs are an emerging initiative whose commitment is oriented towards the transformation of conventional market dynamics, conceiving it as a means to development, rather than an end in itself. The objective of this research is to analyze the behavior of exchange dynamics and characteristics of the actors present in a strategy of short urban-rural marketing circuits in Medellín, between the years 2020 and 2022. A descriptive cross-sectional study is proposed, with availability retrospective data through secondary source. The source of information will correspond to the records of visits and marketing logs concerning the program to strengthen the agri-food system in the District of Medellín for the years 2020 to 2022. The strategy welcomed 306 local producers, of which only 5, 8% belong to associative processes; As for marketers, it was identified that proximity and price are the key characteristics when supplying food; In turn, the transactions generated in the strategy date from marketing mainly of vegetables, generating low quantity transactions mainly in stores and supermarkets, however, when the recipient is the institutional market, a greater volume is evident in the marketing of the foods. The evaluated strategy allowed us to identify how, from an institutional project aimed at the implementation of Short Marketing Circuits in the local environment, effective mechanisms are generated to promote fair trade, improve the conditions of local producers, and provide the territory with food fresh.